Research on HIL-based HVRT and LVRT automated test system for photovoltaic inverters. (November 2021) - Li, Fei; Liu, Mengtao; Wang, Yingfeng; Zhang, Xing
Abstract: As an important capability of the photovoltaic grid-connected inverter, high voltage ride-through (HVRT) and low voltage ride-through (LVRT) capability are related to the stability of the whole power grid system. Therefore, according to the requirements of HVRT and LVRT standards, an automatic test and analysis system of the photovoltaic inverter is designed based on a hardware-in-the-loop (HIL) simulation platform, which saves time and human resources. Firstly, this paper analyzes the specific requirements for HVRT and LVRT capabilities in Q/GDW 1617-2015. Secondly, a HIL simulation platform is built. Thirdly, an automatic test and analysis system is developed based on Python and m language using RT-LAB and Matlab software, which can realize the automation of HVRT and LVRT test, data collection and storage, data processing and standard index calculation, and test results report generation of the photovoltaic inverter under different steady-state conditions. Finally, the correctness of the system is verified on the HIL simulation platform.